Diversity of social wasps (Hymenoptera, Vespidae, Polistinae) in three fragments of semideciduous seasonal forest in the northwest of São Paulo State, Brazil - Gomes,Bruno (2009)
Human exploitation of the forest in the northwest of São Paulo State has generated enormous fragmentation of that forest. Such disturbance has reduced the populations of insects in general. This work was a survey of social wasps (Hymenoptera, Vespidae; Polistinae) in three areas in different stages of regeneration: Paulo de Faria - SP (435 ha), Pindorama - SP (128 ha) and Neves Paulista - SP (1 ha). These three areas were chosen for comparative purposes. To capture the wasps, it was used: active collecting with attractant liquid (solution of water, salt and sugar) with the aid of a dorsal spray bag. During the period from July to December 2006, 414 social wasps were collected in Paulo de Faria, constituting seven species belonging to four genera; 111 social wasps were collected in Pindorama, constituting six species belonging to four genera, and 129 social wasps were collected in Neves Paulista constituting 12 species belonging to seven genera. In order to compare these three areas ecological indexes were calculated. Neves Paulista had the greatest diversity, and Paulo de Faria presented greater abundance. These factors were probably caused by neighboring areas and ecological corridors, which were limited in Paulo de Faria and Pindorama.